Diagnostic and counselling difficulties using a fully comprehensive screening protocol for families at risk for tuberous sclerosis. Issue 11 (November 1989) - al-Gazali, L I; Arthur, R J; Lamb, J T; Hammer, H M; Coker, T P; Hirschmann, P N; Gibbs, J; Mueller, R F
Abstract : Tuberous sclerosis (TS) results from an autosomal dominant gene which exhibits variable expression and reduced penetrance. Although there are well established diagnostic criteria for TS, examination of first degree relatives can cause diagnostic criteria for TS, examination of first degree relatives can cause diagnostic problems with consequent difficulties in genetic counselling. Using an extensive, non-invasive protocol consisting of skin examination with Wood's lamp, cranial CT scan, specialist ophthalmological and dental examination, skeletal survey, and echocardiography, we have examined 56 first degree relatives of persons with TS. These consisted of 40 parents and seven sibs from 25 sporadically affected families and nine persons from seven multigeneration families. In seven of the apparently sporadically affected families, three mothers had echocardiographical findings consistent with one or more rhabdomyoma. In another, the mother's renal ultrasound showed evidence of single cysts in both kidneys. In a fifth family, the father had suggestive but not diagnostic features of TS on the cranial CT scan and skeletal survey. In the sixth family, the mother was found to have atypical calcification on CT scan. In a seventh instance a sib from a two generation family had echocardiographical evidence of a rhabdomyoma. Even though the proband in three of the sporadically affected families presented with fits, developmental delay, and depigmented patches, and therefore did not strictly fulfil the diagnostic criteria for TS, two mothers were found to have evidence of rhabdomyomata on echocardiography and the brother of the third had typical depigmented patches. Although the presently accepted diagnostic criteria for TS may not allow one to make a definitive diagnosis of TS in these relatives, we recommend that an extensive screening protocol be used to examine first degree relatives and that caution be used in counselling apparently unaffected members of families at risk for TS.